Capital Access For Micro Small Medium Enterprises - Evi Christine Tambunan; Kamaludin Enuh; Ubaidullah Ubaidullah; Mariati Tamba (Jurnal Ekonomi dan Perbankan Syariah, 2022)
Along with the development, various factors are needed including in terms of capital which must be continuously fulfilled to continue distribution activities from producers to consumers. Ease of access to capital for MSMEs includes the ease of requirements in applying for formal financing so that business people do not choose personal or non-formal loans which can be said to have less stable capital availability. These easy requirements, even accompanied by light financing services, greatly encourage business people to develop their businesses so that they continue to receive circular financing. The research uses literature research. The data collection method used is the documentation method. The data analysis emphasis on disclosing the content (essence) aspects of several existing propositions. Furthermore, this method is the nature of the review of various theories and analyses. The results of his research SME usually use business capital from personal pockets or joint capital with partners at the beginning of establishing a business. MSMEs are important because compared to large companies, external sources of MSME financing are limited in terms of supply and demand. Business capital can also be interpreted from various aspects, namely capital for the first time to open a business, capital to expand the business, and capital to run daily businesses obtained from the investment model and working capital. MSME constraints on bank credit can be viewed from the demand and supply side. Efforts are being taken to increase the use of credit facilities from banking institutions by micro, small and medium enterprises by increasing access to banking to obtain credit facilities for MSMEs, strengthening MSMEs in financial, managerial, partnership, and entrepreneurial capabilities.